Adult genitourinary sarcoma: Clinical characteristics and survival in a series of patients treated at a high‐volume institution. (3rd May 2017) - Wang, Xianding; Tu, Xiang; Tan, Ping; Zhan, Wenli; Nie, Pan; Wei, Bing; Li, Xiaohong; Chen, Libo; Lu, Yiping; Han, Ping
Abstract : Objectives: To report our institutional experience in the management of adult genitourinary sarcoma. Methods: This was a retrospective analysis of data on adult genitourinary sarcoma treated at the West China Hospital, Sichuan University, Chengdu, Sichuan, China from 1985 to 2010. Clinicopathological parameters were analyzed to determine their impact on overall, recurrence‐free and metastasis‐free survivals. Results: A total of 46 women and 142 men were included, with a median age of 42 years. Of these, 152 cases were high‐grade. The most common site was the paratesticular region. Surgical resection was carried out in 155 patients (82.4%), with negative margin in 106. After a minimum follow up of 5 years, 20 patients (11.6%) survived disease‐free, 14 (8.1%) were alive with disease and 138 (80.2%) died of disease. Survival rates at 1, 3 and 5 years were 91.3%, 64.0% and 47.7%. In univariate analyses, liposarcoma, high grade, metastasis at diagnosis, a lack of surgical resection and positive margin were predictive of unfavorable survival. In multivariate analyses, high grade, a lack of surgical resection and chemotherapy were independent predictors of poor survival. Conclusions: Adult genitourinary sarcoma is an aggressive malignancy, usually presenting at advanced stage, with a high incidence of recurrence and metastasis. Complete resection and selective combination of chemotherapy and radiotherapy might constitute the optimal treatment for this disease.